Instytucja «lidera narodu» w republikach Azji Środkowej. Analiza prawno-porównawcza - Czachor, Rafał (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2019)
Political and legal transformation of post-Soviet republics in Central Asia aimed to introduce state-building and nation-building processes. There were serious changes in the system of state institutions. Newly introduced presidents gained a wide range of competencies and tended to dominate over other institutions, including the governments and parliaments. Strengthening the presidential power was followed by re-traditionalization, which means appreciation of national values, former power and mighty leadership. Extreme evidence of such tendencies was the introduction to the legal system of Kazakhstan, Tajikistan and Turkmenistan of the institution of ‘the leader of the nation’. Such institution ensures incumbents unlimited number of the terms of office and, if they resign from the office, control over the successor. The aim of the paper is to describe the circumstances of the introduction of the institution of ‘the leader of the nation’ in all abovementioned countries and current legal regulations. The author argues that such status stipulates special rights. In all three cases, incumbents are not limited by the term of office, are honored by a dignity Elbasy, Leader the of Nation, Turkmenbashi, Arkadag and are provided by legal and political immunity.
Keywords: instytucja lidera narodu; Azja Środkowa; reformy ustrojowe państw postradzieckich; Kazachstan; Tadżykistan; Turkmenistan